Factors affecting food delivery riders' intention to participate in the gig economy - Shafiei, Azarisham (2022)
This study looked at numerous factors affecting food delivery riders' (FDRs) intention to participate in the gig economy in the wake of the Covid-19 (C19) epidemic. FDRs typically transport prepared food from restaurants to customers. Despite the increased academic interest in a labour market characterized by the prevalence of short-term contracts or better known as the gig economy, the emergence of new types of gig employment, and the factors that inspire workers to participate in the gig economy, few studies have looked at the impact of C19 and its connections to FDRs' participation in the gig economy. In the absence of employment protection, the Push-Pull-Mooring (PPM) theory, with numerous antecedents affecting FDRs, had been used to comprehend factors affecting their participative behaviour. Data was collected from 403 FDRs, 393 of which were valid. SPSS 26.0 and SmartPls version 3.30 software were used to evaluate the data in this study. This study found push variables (economic necessities and extra income) and pull variables (flexibility, control and autonomy) to positively correlate with the FDRs' intention to participate in the gig economy. In comparison, limited alternatives (push variable) and enjoyment (pull variable) were found to have a negative relationship with such intention. This study has also indicated that FDRs will have lower participation due to the lack of employment protection (mooring factor), which moderated the relationship between economic necessities and their participation in the gig economy. The empirical results reported herein should be considered in light of some limitations as it focused on FDRs engaged within the Klang Valley Area and utilized a cross-sectional quantitative method on a section of a targeted population, not the whole population. In conclusion, this study provides some practical suggestions for FDRs that assist critical stakeholders in obtaining good work and living conditions during the C19 pandemic.